Detection of Fatty Acids and Some Secondary Metabolites in Macadamia and Hazelnut Fruits and their Shells, with Studding the Physiochemical Properties of its Extracted Oil: A comparative Study: Deteksi Asam Lemak dan Beberapa Metabolit Sekunder pada Buah Macadamia dan Kemiri serta Cangkangnya, dengan Mempelajari Sifat Fisiokimia Minyak Hasil Ekstraksi: Sebuah Studi Komparatif - Rana T. Altaee; May G Aldabbagh; Aya I. Rashan (Academia Open, 2024)
General Background: Nuts are widely recognized for their nutrient density, offering a rich source of beneficial fatty acids and antioxidant phytochemicals. Specific Background: Among these, macadamia and hazelnuts are popular for their unique compositions, yet direct comparisons of their nutritional and bioactive profiles remain limited. Knowledge Gap: Despite their recognized health benefits, comparative analyses of the fatty acid profiles, bioactive compositions, and physicochemical characteristics between these nuts are scarce. Aims: The study compared macadamia and hazelnut oils' fatty acid content, lipid-soluble vitamins, phenolic compounds, and physicochemical properties to enhance their functional applications. Results: The findings revealed that hazelnut oil exhibited a higher polyunsaturated fat content, particularly linoleic acid (22.8% vs. 18.25%), while macadamia oil contained significantly more vitamin E, contributing to superior antioxidant potential. Both oils demonstrated the presence of vitamins A, D, and K1, with notable concentrations of quercetin and rutin among other flavonoids. Novelty: This study is novel in its comprehensive comparative analysis of these two nuts, particularly in identifying the unique phenolic compounds in the nutshells, which are often discarded but show potential as nutraceuticals. Implications: Macadamia and hazelnut oils offer significant nutritional benefits, with compositional variations allowing for personalized bioactivity and culinary applications. Further research is recommended for human health promotion. Highlights: Hazelnut oil has more polyunsaturated fats; macadamia oil is richer in vitamin E. Both nuts contain vitamins A, D, E, K1, and flavonoids. Phenolic compounds in nutshells have potential as nutraceuticals. Keywords: macadamia nuts, hazelnut oil, fatty acids, antioxidant phytochemicals, bioactive compounds